Dysregulated mitogen-activated protein kinase and matrix metalloproteinase in ethanol-induced cavernosal dysfunction - Muniz, Jaqueline J; Leite, Letícia N; Lacchini, Riccardo; Tanus-Santos, José E; Tirapelli, Carlos R (Canadian journal of physiology and pharmacology, 2018)
We evaluated the effects of ethanol consumption on the mitogen-activated protein kinases (MAPK) and metalloproteinases (MMP) pathways in the rat cavernosal smooth muscle (CSM). Male Wistar rats were treated with ethanol (20% v/v) for 6 weeks. Quantitative real-time polymerase chain reaction experiments showed that ethanol consumption did not alter mRNA levels of p38MAPK, SAPK/JNK, ERK1/2, MMP-2, or MMP-9 in the rat CSM. Western immunoblotting experiments revealed decreased protein expression of p38MAPK and phosphorylation of SAPK/JNK in the CSM from ethanol-treated rats. Additionally, ethanol consumption decreased the expression of MMP-2. Functional assays showed that SP600125, an inhibitor of SAPK/JNK, prevented the increase in endothelin (ET)-1-induced contraction in the CSM from ethanol-treated rats. Treatment with ethanol decreased MMP-2 activity, but did not change net MMP activity in the rat CSM. Ethanol consumption increased the circulating levels of MMP-2, MMP-9, and TIMP-2 as well as the MMP-9/TIMP-1 ratio. The major finding of our study is that ethanol consumption down-regulates both MAPK and MMP pathways in the rat CSM, whereas it increases the circulating levels of MMP-9. Additionally, we found that SAPK/JNK plays a role in ethanol-induced increase on ET-1 contraction in the isolated rat CSM.